1998
DOI: 10.1046/j.1365-2257.1998.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe bactrim-induced neutropenia with reversal of CD4+ /CD8+ lymphocyte ratio: response to recombinant human granulocyte-colony stimulating factor (R-metHUG-CSF)

Abstract: A patient presented with severe bactrim-induced neutropenia with a reversed CD4+/CD8+ lymphocyte ratio. R-metHUG-CSF at 300 micrograms daily produced a dramatic neutrophil response and the therapy was discontinued after 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…9 We conducted a review of published cases (Table 2) and noted that the majority of identified cases of agranulocytosis with sulfamethoxazole/trimethoprim reported in the literature were associated with medically complex patients, concomitant medications that may contribute to agranulocytosis, or extended courses of sulfamethoxazole/trimethoprim therapy. [10][11][12][13][14][15][16][17][18] From the review of the literature, it can also be noted that many cases were missing key patient level details such as concomitant medications/comorbidities which limit the ability to interpret likelihood without that key clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…9 We conducted a review of published cases (Table 2) and noted that the majority of identified cases of agranulocytosis with sulfamethoxazole/trimethoprim reported in the literature were associated with medically complex patients, concomitant medications that may contribute to agranulocytosis, or extended courses of sulfamethoxazole/trimethoprim therapy. [10][11][12][13][14][15][16][17][18] From the review of the literature, it can also be noted that many cases were missing key patient level details such as concomitant medications/comorbidities which limit the ability to interpret likelihood without that key clinical context.…”
Section: Discussionmentioning
confidence: 99%